Where did the salt go? - Siba Prosad Paul; Sarah Sian Hicks; Manjunath Kariyappa Sanjeevaiah; Paul Anthony Heaton (The Turkish Journal of Pediatrics)
Bronchiolitis is a self-limiting viral respiratory-tract-infection seen commonly in infants. Some infants require hospitalization for feeding or respiratory support. A wide range of extra-pulmonary complications such as arrhythmias, myocarditis, central apneas, seizures, and hyponatremia are uncommonly known to occur with respiratory syncytial virus (RSV) infections. We present a 4-week-old-female infant admitted with RSV bronchiolitis for feeding support by nasogastric-tube. The infant suffered unexpected desaturations and seizure-like event 30-hours post-admission. Severe hyponatremia (sodium: 114 mmol/L) was detected although cause for this remained unexplained initially. Serum sodium improved following a bolus of 2.7% hypertonic-saline. The infant subsequently needed advanced respiratory support. Around time of transfer to PICU, the infant developed abdominal distension and continued to have bilious aspirate even after 6-days. An upper gastrointestinal contrast-study confirmed malrotation; improved following surgery. Co-existence of two serious pathologies may have accounted for the hyponatremia: malrotation (possible source of sodium loss into third-space) and severe bronchiolitis (inappropriate ADH-secretion). This case highlights the importance of determining origin of hyponatremia associated with acute bronchiolitis.